Remarks About Legal Situation of Animal Injured By Prohibited Act in Polish Criminal Process - Mazur, Paweł (ETHICS IN PROGRESS, 2018)
The article is focused on the issues relating to a legal situation of an animal as a victim of a criminal offense. Currently, according to the rules of criminal procedure, an animal, as an entity, cannot be legally recognised a victim, which significantly lowers efficiency with which its interests can be protected. There are strong moral and pragmatic reasons to grant animals the status of a non-personal carrier of legal rights. Legal personality of animals as victims during a criminal trial should be of only passive nature, allowing recognition of legally-protected interests of the animal.